(untitled) (Nigerian Journal of Technology, 2025)
Structural cracks in buildings present significant safety and integrity challenges, necessitating thorough investigation into causes, effects, and repair strategies. This study explored factors contributing to structural cracks, their implications on the structural members and building as a whole, and various repair methods from the literature. The factors were populated in questionnaires to acquire feedback from respondents with and without knowledge of crack propagation in buildings. Through analysis and observation, including survey insights and visual measurements, diverse causes emerged, from material deficiencies to environmental influences. 81% of respondents understood structural cracks, with 68% aware of common causes that are sometimes neglected. Initial thin cracks, if ignored, can escalate into serious issues and jeopardize safety. 80% of respondents would not inhabit aesthetically compromised buildings due to cracks. Repair strategies are critical to address the underlying causes and factors affecting the cracking of structural members. This will involve efforts from architects, engineers, contractors, and occupants through educational initiatives and awareness campaigns to enhance collective understanding of the impending problems and prevention measures to avoid incessant building collapse.